Molecular identification of Eurycoma longifolia Jack from Sumatra, Indonesia using trnL-F region - KUSUMADEWI SRI YULITA; ARIDA SUSILOWATI; HENTI HENDALASTUTI RACHMAT; SUSILA SUSILA; ASEP HIDAYAT; FIFI GUS DWIYANTI (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Yulita KS, Susilowati A, Rachmat HH, Susila, Hidayat A, Dwiyanti FG. 2022. Molecular identification of Eurycoma longifolia Jack from Sumatra, Indonesia using trnL-F region. Biodiversitas 23: 1374-1382. Eurycoma longifolia Jack (Simaroubaceae) or pasak bumi is a popular medicinal plant from Southeast Asia’s rainforests that is used as an aphrodisiac, antimicrobial, anti-malaria antidiabetic, antiulcer, and anticancer agent. However, the increasing demand for this species for medicinal industries has led to illegal export in Indonesia. This study aimed to determine the specific genetic variation and develop DNA barcode using trnL-Fregion for E. longifolia originating from Sumatra, Indonesia. Twenty-two samples of the species were collected from four locations in Sumatra. An aligned sequence of the trnL-Fwas 960 bp with an A/T rich region (A: 30.2%, T: 34.5%, C: 16.7%, and G: 18.7%). The homology search using BLASTn of the GenBank NCBI showed that the nucleotide composition of the species was similar (99.9%) to the partial trnL-Fregion of E. longifolia MH751519 and E. apiculata GU593014. Close examination of the gene structure and composition showed that the DNA sequences have five nucleotides variations that were not possessed by the reference E. longifolia, and other taxa used. The obtained variations occurred mostly in the trnL intron region, and the phylogenetic analysis showed that the correct identity of the species of the samples by their position was at a similar clade as the other accessions of E. longifolia.